Real Wage Rigidities, Fiscal Policy, and the Stability of EMU in the Transition Phase - Thode, Eric.; Berthold, Norbert; Fehn, Rainer (Washington, D.C. : International Monetary Fund, 1999)
EMU started with eleven member countries as scheduled on January 1, 1999. The paper shows that the primacy of politics over economics in this decision could have serious consequences concerning the stability of EMU in the transition phase. Speculative attacks against currencies which are in economic distress due to asymmetric shocks can still happen. A speculative attack as such cannot force a country out of EMU. However, the country concerned might voluntarily decide to leave the system as the costs of staying inside EMU, e.g., due to further rising unemployment, become too large to bear.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet